Application of a liquid chromatographic method for the determination of phenolic compounds and furans in fortified wines - Ho, P. (2011)
Fortified wines which suffer extended periods of wood ageing develop characteristics which in many cases define the product. An important component of this style is contributed by the specific phenolic compounds and furans which are either extracted from the wood or formed during the barrel ageing process. An HPLC method is presented here for the determination of phenolic compounds and furans in wood aged fortified wines. The method employed involved direct injection with no sample pre-treatment, separation on a RP C18 column in a single run and detection with a diode array detector. In this way up to 28 compounds from various phenolic groups (hydroxybenzoic acids, hydroxycinnamic acids, phenolic aldehydes, coumarins, ¯avan-3-ols, ¯avonol aglycones and other compounds involved in browning reactions in food systems (furans and pyranones) could be separated and determined. Of these, 10 phenolic compounds, gallic acid, protocatechuic acid, p-coumaric acid, ca eic acid, chlorogenic acid, ellagic acid, vanillic acid, syringic acid, p-hydroxybenzaldehyde, myricetin, and two furans; furfural, 5-hydroxymethyl-2-furaldehyde, were determined in forti®ed and similar wood aged wines. Three other compounds, a chlorogenic acid isomer, vanillin and resorcinol, were also tentatively identified in these wine types